Critical and Inclusive Education. The Value of Difference in a School Without Exclusions (book review) - Farzaneh Peña, Diana (Márgenes, Revista de Educación de la Universidad de Málaga, 2025)
This book review highlights Critical Education and Inclusion. The Value of Difference in a School Without Exclusions as an essential contribution to rethinking public education through a commitment to equity, social justice, and the recognition of difference. Rather than treating inclusion as a distant goal, the authors present it as an immediate principle of action, supported by strong theoretical foundations and practical strategies. The review underscores the book’s dialogical and accessible tone, and its ability to engage educators committed to a critical, humanizing, and collective teaching practice.